From genios to unhappy consciousness. Schlegel versus Kant and idealism - López-Farjeat, Luis Xavier (Estudios de Filosofía, 1998)
The notion of genius used by Witz was first defined by Shafiesbury and later used by Kant and Fichte. Genius is thought as a kind of link between Nature and Freedom as apparent poles. Hence, only but genius can connect Hellenic harmony and Romantic misharmony. Starting from this idea, the author first exposes the relationships between genius, nature and freedom (Kant). He then refers to this trial of conciliation, which is the core of modern poetry (Schlegel, Goethe), and which ends in genius disappointment, in the Hegelian unhappy consciousness.